2000
DOI: 10.1093/oxfordjournals.bja.a013445
|View full text |Cite
|
Sign up to set email alerts
|

Residual curarization in the recovery room after vecuronium

Abstract: We have investigated residual block after anaesthesia which included the use of the neuromuscular blocking agent vecuronium but no anticholinesterase, in 568 consecutive patients on admission to the recovery room. The ulnar nerve was stimulated submaximally using TOF stimulation (30 mA). Postoperative residual curarization was defined as a TOF ratio < 0.7. Of the 568 patients, 239 (42%) had a TOF < 0.7 in the recovery room. These patients had received a larger cumulative dose of vecuronium than patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(90 citation statements)
references
References 0 publications
3
81
1
5
Order By: Relevance
“…Baillard et al [21] defined PORC as TOF falling below 70% after extubation and reported the incidence of PORC in the recovery room was 42%. In spite of the use of neostigmine to reverse the effects of muscle relaxant agents, development of PORC may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Baillard et al [21] defined PORC as TOF falling below 70% after extubation and reported the incidence of PORC in the recovery room was 42%. In spite of the use of neostigmine to reverse the effects of muscle relaxant agents, development of PORC may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…La incidencia de BNMR presenta una gran variabilidad con porcentajes que oscilan entre el 2% y el 64% 87,93,94,95,96,97,98,99,100,101,102,103,104,105 .…”
Section: Incidencia De Bnmrunclassified
“…In a study examining neuromuscular block induced with vecuronium, Baillard et al [42] reported a higher median age in a group of patients with a detected PORC defined as TOFR < 0.7 compared to patients with greater TOFR values. This was confirmed by the results of two large prospective studies with residual blockade as the primary end-point in elderly patients after the administration of rocuronium [5,43].…”
Section: Residual Neuromuscular Block As a Significant Clinical Problmentioning
confidence: 99%